(3GdebUO GdMSf hGdeSdc GdhGVM GdSff aj eG dG jfHZi Lgdg dPhi Gdabg hGdaWf ef dhGRe Yde GdaQGFV hGdSffs - (3CMeO Hf jMji Hf CMeO Hf MGHS GdOhGQj GdUYOj,J (B1061 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai hHYO aEf Yde GdaQhY GdabgjI de cGf eSGS GdMGLI Edjg CcKQ ef SGFQ GdYdhe s
(3BNQgG (B:s
(3hGYde Cf GdZfGFe cGfJ ai TQY ef bHdfG dGjLhR JedcgG hGddg CYde s
(3GdfSNI HgG MhGTs
(3GfJgi ef JCdjag SfI (B1052(3g`s
(3fSNI eUMMI s
(3cJHJ GdYfGhjjf hGdahGJM HGdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdESdGejs